2018
DOI: 10.1093/mnras/sty2711
|View full text |Cite
|
Sign up to set email alerts
|

Dark Energy Survey Year 1 results: weak lensing mass calibration of redMaPPer galaxy clusters

Abstract: This document is made available in accordance with publisher policies and may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the URL above for details on accessing the published version.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
330
9
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(361 citation statements)
references
References 102 publications
15
330
9
2
Order By: Relevance
“…With optical-surveys, optical-richness (Rykoff et al 2016;Farahi et al 2019b) and total stellar mass (Palmese et al 2019) have emerged as a potential low scatter proxy of halo mass to perform cosmological analysis (Costanzi et al 2019b). The statistical parametric models, such as the linear model employed here, are readily applicable to observational data, and the parameters can be inferred directly from the data (McClintock et al 2019). Our results suggest that splitting the total stellar mass into satellite and BCG components might improve the precision of halo mass estimation, which can be explained via the correlation between BCG mass and the age of halo (Bradshaw et al 2019).…”
Section: Improving Mass Estimationmentioning
confidence: 79%
See 1 more Smart Citation
“…With optical-surveys, optical-richness (Rykoff et al 2016;Farahi et al 2019b) and total stellar mass (Palmese et al 2019) have emerged as a potential low scatter proxy of halo mass to perform cosmological analysis (Costanzi et al 2019b). The statistical parametric models, such as the linear model employed here, are readily applicable to observational data, and the parameters can be inferred directly from the data (McClintock et al 2019). Our results suggest that splitting the total stellar mass into satellite and BCG components might improve the precision of halo mass estimation, which can be explained via the correlation between BCG mass and the age of halo (Bradshaw et al 2019).…”
Section: Improving Mass Estimationmentioning
confidence: 79%
“…For example, in the context of modeling star formation, a log-normal shape for final stellar mass naturally emerges when random factors govern the evolution of the system (e.g., Larson 1973;Zinnecker 1984). In the past decade, observations (Pratt et al 2009;Reichert et al 2011;Mahdavi et al 2013;Lieu et al 2016;Mantz et al 2016a,b;McClintock et al 2019;Golden-Marx & Miller 2019;Mulroy et al 2019) and simulations (Evrard et al 2008;Stanek et al 2010;Truong et al 2018;Farahi et al 2018;Bradshaw et al 2019) have employed the power-law, log-normal model and extensively studied and quantified the mean and scatter of mass-observables relation. These studies found that the a powerlaw model with a log-normal scatter is a sufficient model to describe integrated properties of the most massive systems.…”
Section: Introductionmentioning
confidence: 99%
“…where D = (∆Σ obs − ∆Σ model ) is the differences between the observed and modeled excess surface mass density, and C is the covariance matrix described in Section 4.2 (e.g. McClintock et al 2019a).…”
Section: Mcmc Methodsmentioning
confidence: 99%
“…The vector ∆Σ is the average of the excess surface mass density profile of all clusters (e.g. McClintock et al 2019a). We assume that cluster measurements are uncorrelated, and therefore, that the covariance matrix is diagonal.…”
Section: Individual Cluster Covariancementioning
confidence: 99%
See 1 more Smart Citation